Comparison of soft tissue mobilization versus static stretching in post-burn contractures at elbow and wrist, A pilot study - Zainab Tehreem; Yasir Kazmi; Muhammad Usman Khalid; Haroon Mansha; Muhammad Hassan; Rabia Majeed (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Post-burn contracture is the tightening of the skin after a second or third-degree burn with the formation of contracture. Post-burn contractures result in the limitation of movement around a burn area. Burns contractures, if left untreated, may cause limitations in the range of motion and daily living tasks. The purpose of this study was to compare the effects of soft tissue mobilization versus static stretching in post-burn contractures at the elbow and wrist. METHODOLOGY: A pilot study was conducted, and 36 patients were enrolled. Patients with post-burn contracture were divided randomly into two groups. Allocation of patients in both groups was done by computerized generated list. The treatment frequency was 3 times a week. Numeric pain rating scale (NPRS) and Katz index ADLS scale were used for scoring. Paired t-test was applied to evaluate the data. RESULTS: The mean age in group A and B were 26.16±7.46 and 28.05±1.27, respectively. Mean score for pre-Katz Index of Group A and B (2.47±0.87, 2.16±0.98), post-Katz Index group A and B (3.29±1.68, 3.05±1.47) with a p-value 0.12 and 0.03 group A and B respectively. The mean score group A and B for pre-NPRS (7.61±1.37, 7.94±1.10), post-NPRS (2.27±1.01, 1.72±1.22) with a p-value<0.001 . CONCLUSION: It was concluded that static stretching is more effective than soft tissue mobilization.